PENGARUH TERAPI MUROTTAL AL-QUR’AN SURAH AR-RAHMAN TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKEMAS MERDEKA PALEMBANG - Setiawan; Rahmalia Afriyani (Jurnal Kesehatan dan Pembangunan, 2022)
ABSTRACT Hypertension is a condition in which a person has an increase in blood pressure above normal, which is equal to or more than 140/90 mmHg. Efforts to deal with hypertension can be done in a non-pharmacological way, namely by using the Murottal Al-Qur’an Surah Ar-Rahman therapy. This study aims to determine the effect of murottal Al-Qur’an Surah Ar-Rahman therapy on reducing blood pressure in hypertensive patients. This research design uses a pre-eksperimen method with a one group pretest-posttest approach. The population in this study were hypertensive patients who were treated in the working area of the Palembang Merdeka Health Center with a sample of 25responden. Data were analyzed by univariate analysis and bivariate analysis. The results of the univariate analysis showed that the mean systolic and diastolic blood pressure before the Surat Ar- Rahman murottal therapy was 150,00 mmHg for systolic and 93,00 mmHg for diastolic while after treatment was 145,00 mmHg for systolic and 90,00 mmHg diastolic. In the bivariate analysis a nonparametric test was used namely the wilcoxon test with the results of p-value = 0,000 < α 0,05 for systolic and diastolic before while systolic and diastolic after treatment obtained p-value = 0,000 < α 0,05. So it can be concluded that there is an effect of murottal Al-Qur’an therapy Surah Ar-Rahman on reducing blood pressure in hypertension sufferers in the working area of the Palembang Merdeka Health Center Keyword : Hypertension, Murottal Al-Qur’an Therapy, Blood Pressure